(untitled) (International Journal of Physiotherapy, 2024)
Background: Work-related low back pain (LBP) is a common musculoskeletal disorder related to work and contributes to decreased employee health and productivity. Physical therapists (PTs) are more susceptible to developing LBP than other healthcare employees. Although LBP might contribute to decreased quality of life (QoL) among PTs, factors underpinning correlations between work-related musculoskeletal disorders and QoL among PTs are not substantiated. This study aimed to investigate correlations between work-related LBP and QoL among PTs. Methods: This cross-sectional study used an online survey completed by PTs. The survey form was based on a previously published questionnaire for assessing the experience of work-related LBP and the 36-Item Short Form Health Survey for evaluating QoL. The dependent variable was QoL; the independent variables were LBP rating, how LBP impacted the work of the PTs, weekly hours of direct patient contact, experience as a PT, and income. Results: A total of 690 PTs, consisting of males (375) and females (315), completed the survey form. Correlation analysis revealed significant correlations between QoL and the following variables: income (r=0.42, p < 0.01), LBP impact on participant’s job performance (r=0.41, p < 0.01), experience as a PT (r=0.17, p < 0.01), weekly hours of direct patient contact (r=0.11, p < 0.01), rating of LBP (r=-0.64, p < 0.01) and area of PT specialty (r=-0.15, p < 0.01). Conclusions: The study showed correlations related to multiple factors between QoL and work-related LBP among PTs. Further investigation is needed to obtain more knowledge about these correlations.